Penerapan Metode Naïve Bayes dalam memprediksi Peluang Kerja untuk Penyandang Disabilitas - Yuliadarnita Yuliadarnita; Ridho ikram; Rozali Toyib (UNIVED Press, 2025)
The right to get a job is a right that is owned by all members of Indonesian society, including those with disabilities. This has been regulated in the constitution, but the opportunities for individuals with disabilities to get a job are much less than the wider community. Those with disabilities often have difficulty finding work because many companies do not take them into account, assuming that people with disabilities cannot contribute well because of the limitations they have. The Naive Bayes method has several advantages, such as the simplicity of the model, but can still compete with other algorithms. The test results if the value of the calculation is 100% then people with disabilities can work in that job and if the value is less than 100% then people with disabilities cannot work in that job, the calculation results from the table can be concluded that the predicted jobs for people with disabilities are: Tailors (K4), Graphic designers (K5), and Archivists (K6), The application process is also not too complicated, very suitable for assessing conditional probability, and very fast because the probability can be calculated directly. The speed in training this model is very high, especially if the conditional independence assumption is met, it can be sure to produce good performance, but its main drawback is that it requires the condition that all predictors are independent.